Electrolyte additive, electrolyte and lithium ion battery

CN122992174APending Publication Date: 2026-10-27HEFEI QIANRUI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611473883.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]基于背景技术存在的技术问题,本发明提出了一种电解液添加剂、电解液和锂离子电池,以解决现有技术中锂离子电池的硅碳负极在长循环过程中发生体积膨胀、SEI膜破裂、活性锂和电解液不断消耗,致使容量快速衰减、循环性能恶化的问题,通过所述添加剂的引入,能够在硅碳负极表面构筑一层稳定、致密且能适应巨大体积变化的SEI膜,从而显著提升锂离子电池的首次库仑效率、循环寿命和倍率性能,推动高能量密度硅碳电池的商业化进程

Benefits of technology

(1)本发明提出了一种新型电解液添加剂,优点在于其多功能协同作用机制,该添加剂同时具备高反应活性的-NCO基团和强电负性的-CF3基团,可抑制副反应对硅碳负极的腐蚀,并优先成膜。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992174A_ABST
    Figure CN122992174A_ABST
Patent Text Reader

Abstract

The application provides an electrolyte additive, an electrolyte and a lithium ion battery, and aims to solve the problems that the silicon-carbon negative electrode of the lithium ion battery in the prior art is subjected to volume expansion, the SEI film is broken, active lithium and electrolyte are continuously consumed, the capacity is rapidly attenuated, and the cycle performance is deteriorated in a long cycle process; through the introduction of the additive, a stable, dense and adaptable SEI film capable of adapting to great volume change can be constructed on the surface of the silicon-carbon negative electrode, so that the first coulomb efficiency, the cycle life and the rate performance of the lithium ion battery are significantly improved, and the commercialization process of the high-energy-density silicon-carbon battery is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrolyte technology, and more particularly to an electrolyte additive, an electrolyte, and a lithium-ion battery. Background Technology

[0002] To overcome the energy density bottleneck of traditional graphite anodes, silicon-carbon composite materials have become the mainstream development direction for next-generation high-energy-density lithium-ion battery anodes. This material aims to combine the high specific capacity of silicon with the excellent conductivity and structural stability of carbon materials, forming a complementary advantage. However, silicon-carbon anodes are not simply the sum of the performance of the two materials; their practical application still faces severe challenges stemming from their composite structure. The significant volume expansion during cycling leads to the continuous rupture and regeneration of the solid electrolyte interphase (SEI) membrane, causing continuous consumption of active lithium and electrolyte, resulting in rapid capacity decay and deterioration of cycle performance.

[0003] Currently, commonly used electrolyte additives in silicon-carbon anode systems mainly include film-forming additives such as fluoroethylene carbonate (FEC) and vinylene carbonate (VC). These additives preferentially reduce and decompose on the anode surface to form an electrolyte interphase (SEI) film, thus inhibiting the continued decomposition of the electrolyte to some extent. However, these traditional additives have significant limitations: FEC has poor thermal stability at high temperatures and easily decomposes to produce acidic substances such as HF, which corrode the SEI film; while VC tends to form a thicker SEI layer, increasing battery impedance and having limited adaptability to volume expansion.

[0004] Therefore, developing a novel electrolyte additive specifically for silicon-carbon composite anodes is crucial. This additive should preferentially undergo a controlled reaction on the anode surface to construct a dense, robust interfacial film with excellent mechanical adaptability. This ideal interfacial film must effectively passivate silicon active sites, inhibit continuous electrolyte decomposition, without compromising the conductive network and structural integrity of the carbon matrix, and buffer internal stress to maintain stable electrical contact between silicon and carbon. This would fundamentally and simultaneously improve the initial efficiency, cycle life, and rate performance of silicon-carbon anodes, driving their large-scale commercial application. Summary of the Invention

[0005] Based on the technical problems existing in the background technology, this invention proposes an electrolyte additive, an electrolyte, and a lithium-ion battery to solve the problems of volume expansion, SEI film rupture, and continuous consumption of active lithium and electrolyte in the silicon-carbon anode of lithium-ion batteries during long-term cycling, resulting in rapid capacity decay and deterioration of cycle performance. By introducing the additive, a stable, dense SEI film that can adapt to huge volume changes can be constructed on the surface of the silicon-carbon anode, thereby significantly improving the first coulombic efficiency, cycle life, and rate performance of lithium-ion batteries, and promoting the commercialization of high-energy-density silicon-carbon batteries.

[0006] This invention proposes an electrolyte additive comprising a trifluoromethyl-containing benzene isocyanate as shown in structural formula A:

[0007] Where the number of substituents a is any integer from 0 to 4, and any R 1 An electron-withdrawing group that is independently any one of halogen, haloalkane, cyano, nitro, sulfone, sulfonic acid, carboxyl, or ester.

[0008] In this invention, the trifluoromethyl-containing benzene isocyanate shown in structural formula A is used as a film-forming additive. On the one hand, the isocyanate it contains can react with trace amounts of water and HF to generate inert products, thereby inhibiting the corrosion of the high-nickel / lithium-rich cathode by HF, reducing transition metal dissolution, and lowering the risk of battery gas generation. Both isocyanate and trifluoromethyl are strongly electronegative, which can absorb oxygen free radicals in the electrolyte to the greatest extent, avoiding corrosion of the SEI film caused by electrolyte decomposition. On the other hand, the isocyanate and trifluoromethyl are meta-distributed on the benzene ring, and the combination of their electron-withdrawing effects increases the electron cloud density on the benzene ring. The relative ortho or para position distribution is further reduced. Such low LUMO orbital energies allow for preferential reduction and decomposition at both the positive and negative electrode surfaces, forming a dense nitrogen- or carbon-containing SEI film at the negative electrode and an antioxidant CEI film at the positive electrode, preventing the continuous decomposition of the electrolyte solvent. This dense and stable solid electrolyte interphase (SEI) film reduces interfacial impedance, suppresses volume expansion, and exhibits high ionic conductivity and mechanical strength. Furthermore, the benzene ring structure contributes to the high stability of the interfacial film, and the -CF3 group promotes the formation of low-resistance components such as LiF and nitrogen-containing polymers, further reducing interfacial impedance and enhancing Li... + Improved transmission efficiency, rate performance, and cycle life; stable interface film with uniform Li + Deposition, -CN coordinates with transition metal ions, reduces side reactions of dissolved metals at the negative electrode, improves battery safety, and avoids dendrites piercing the separator and causing short circuits.

[0009] Preferably, the trifluoromethyl-containing benzene isocyanate represented by structural formula A is at least one of the following structural formulas I-VI: .

[0010] Among them, the CAS number for the phenyl isocyanate represented by structural formula I is 329-01-1, the CAS number for the phenyl isocyanate represented by structural formula II is 2369052-28-6, the CAS number for the phenyl isocyanate represented by structural formula III is 143782-18-7, the CAS number for the phenyl isocyanate represented by structural formula IV is 88330-63-6, the CAS number for the phenyl isocyanate represented by structural formula V is 327-78-6, and the CAS number for the phenyl isocyanate represented by structural formula VI is 50528-86-4.

[0011] Preferably, the electrolyte additive further includes phenyl sulfide represented by structural formula B:

[0012] Where the number of substituents b is any integer from 0 to 5, and any R 2 R is an electron-donating group selected from alkyl, alkoxy, alkylamino, aryloxy, or thioether groups. 3 It is a C1-C6 alkyl or aryl group.

[0013] In this invention, based on the trifluoromethyl-containing benzene isocyanate shown in structural formula A, a benzene sulfide shown in structural formula B is added. Due to the strong electron-withdrawing effect of the substituents on the trifluoromethyl-containing benzene isocyanate shown in structural formula A, the benzene ring exhibits a positive charge, while the electron-donating effect of the substituents on the benzene sulfide shown in structural formula B, the benzene ring exhibits a negative charge. The two combine to form a charged complex, acting as donor and acceptor respectively. This further optimizes the interfacial stability of the additive and improves the ionic conductivity of the electrolyte. Furthermore, compared to the presence of thiols or electron-withdrawing substituents on the benzene ring, the presence of active hydrogen or electron-withdrawing groups would be detrimental to the complexation effect of the benzene sulfide shown in structural formula B and the trifluoromethyl-containing benzene isocyanate shown in structural formula A.

[0014] Preferably, the phenyl sulfide represented by structural formula B is at least one of the following structural formulas VII-IX: .

[0015] Among them, the phenyl sulfide represented by structural formula VII has the CAS number 2388-74-1, the phenyl sulfide represented by structural formula VIII has the CAS number 2388-50-3, and the phenyl sulfide represented by structural formula IX has the CAS number 30723-54-7.

[0016] Preferably, the mass ratio of the trifluoromethyl-containing benzene isocyanate shown in structural formula A to the phenyl sulfide shown in structural formula B is 3-5:1.

[0017] The present invention also proposes a lithium-ion battery electrolyte, comprising an electrolyte lithium salt, an organic solvent, and the above-mentioned electrolyte additives.

[0018] Preferably, the electrolyte lithium salt is at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium difluorophosphate (LiPO2F2), or lithium difluorooxalate borate (LiODFB). The amount of the electrolyte lithium salt added is 8-15% based on the total mass of the electrolyte.

[0019] Preferably, the organic solvent is at least one selected from organic esters, alkyl ethers, cyclic ethers, sulfones, dinitriles, and ionic liquids; The organic esters are at least one of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, butenyl carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, propyl propionate, ethyl propionate, ethyl acetate, methyl acetate, or γ-butyrolactone; the alkyl ethers are at least one of 1,2-dimethoxyethane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, or 1,3-dioxolane; the cyclic ethers are at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 4-methyl-1,3-dioxolane, or crown ethers; the sulfones are at least one of sulfolane, methyl sulfolane, ethyl methyl sulfone, or dimethyl sulfone; the dinitriles are at least one of succinic anionibacterium, adiponitrile, glutaronitrile, or 3-methoxypropionitrile; and the ionic liquids are at least one of imidazoles, pyrroles, quaternary ammonium salts, or quaternary phosphonium salts. The amount of organic solvent added is 70-92% based on the total mass of the electrolyte.

[0020] Preferably, the amount of electrolyte additive added is 0.1-5 wt% based on the total mass of the electrolyte.

[0021] The present invention also proposes a lithium-ion battery, comprising a negative electrode, a positive electrode, a separator disposed between the negative electrode and the positive electrode, and the electrolyte described above.

[0022] Preferably, the active material of the positive electrode is at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, or lithium manganese iron phosphate; preferably lithium nickel cobalt manganese oxide.

[0023] Preferably, the active material of the negative electrode is at least one of silicon-carbon, graphite, silicon oxide, lithium metal, lithium titanate, or silicon dioxide; more preferably, it is a mixture of silicon-carbon and graphite, with a theoretical specific capacity of about 600 mAh / g.

[0024] Preferably, the diaphragm is at least one of polypropylene (PP), polyethylene (PE) diaphragm or glass fiber diaphragm; preferably, it is a polypropylene (PP) diaphragm.

[0025] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention proposes a novel electrolyte additive with the advantage of its multifunctional synergistic mechanism. The additive has both highly reactive -NCO groups and strongly electronegative -CF3 groups, which can suppress the corrosion of silicon-carbon anode by side reactions and preferentially form films.

[0026] (2) The present invention provides a lithium-ion battery electrolyte that can construct a stable SEI film on the negative electrode, and has both high ionic conductivity and good mechanical strength. It can effectively alleviate the huge volume expansion of silicon-carbon negative electrode during charging and discharging, and improve the cycle stability of the battery. Attached Figure Description

[0027] Figure 1 The cycling curves of the pouch cells of Example 1 and Comparative Example 1 at a rate of 0.5 / 1C are shown. Figure 2 The first / 1000 charge-discharge curves of the pouch cells of Example 1 and Comparative Example 1 at a 0.5C rate are shown. Detailed Implementation

[0028] The technical solution of the present invention will be described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention.

[0029] Example 1 A lithium-ion battery electrolyte is prepared by the following method: In an argon glove box with a water and oxygen content of ≤0.1ppm, lithium hexafluorophosphate (LiPF6) was added to a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and fluoroethylene carbonate (FEC) in a mass ratio of 3:5:2:1. The mixture was stirred at room temperature until completely dissolved to obtain a 1mol / L LiPF6 electrolyte. Then, a trifluoromethyl phenyl isocyanate of Formula I was added, with the amount of trifluoromethyl phenyl isocyanate of Formula I being 1wt% of the total electrolyte mass. After stirring and mixing evenly, the lithium-ion battery electrolyte was obtained.

[0030] A lithium-ion battery is prepared by the following method: (1) The ternary material of nickel cobalt manganese oxide (NCM78), conductive agent carbon black and binder polyvinylidene fluoride are mixed in a mass ratio of 94:3:3, and then N-methylpyrrolidone is added. The mixture is stirred using a vacuum mixer to obtain a positive electrode slurry. The positive electrode slurry is uniformly coated on an aluminum foil with a thickness of 12μm using a coating machine. After drying, rolling and cutting, a positive electrode sheet is obtained. The obtained positive electrode sheet is baked in a vacuum oven before use to remove trace water. (2) The negative electrode materials silicon carbon and graphite are mixed in a mass ratio of 17:83 to form a composite active material. The composite active material, carbon black, thickener sodium carboxymethyl cellulose, and binder styrene-butadiene rubber are mixed in a mass ratio of 94:1.5:1.5:3. Deionized water is added and the mixture is stirred using a vacuum mixer to obtain a negative electrode slurry. The negative electrode slurry is uniformly coated on a copper foil with a thickness of 8μm using a coating machine. After drying, rolling, and cutting, a negative electrode sheet is obtained. The obtained negative electrode sheet is baked in an oven before use to remove trace amounts of water. (3) The positive electrode, negative electrode and polypropylene separator prepared above are wound into a cell with a positive and negative N / P ratio of 1.1. The cell is wrapped with an aluminum-plastic film and baked in an oven at 45°C for 24 hours to reduce the moisture content of the battery to below 200ppm. Then the electrolyte is injected and the cell is sealed. After formation and capacity testing, the soft-pack battery is obtained.

[0031] Examples 2-15 and Comparative Examples 1-9 were prepared according to the preparation method described in Example 1, except that the additive components in the electrolyte were changed, as shown in Table 1 below. Electrochemical tests were performed on the pouch cells of the examples and comparative examples. The test items and methods are as follows: (1) 0.5C long cycle test: The cell was placed in a 25℃ constant temperature test cabinet for 3 hours and charged and discharged at a rate of 1 / 3C. After 3 cycles, the discharge capacity C0 of the last cycle was marked. Then, it was charged and discharged at a rate of 0.5C0. The charging and discharging range was 2.8V to 4.25V. Cyclic test was performed. (2) 1C long cycle test: The cell was placed in a 25℃ constant temperature test cabinet for 3 hours and charged and discharged at a 1 / 3C rate. After 3 cycles, the discharge capacity C0 of the last cycle was marked. Then, it was charged and discharged at a 1C0 rate. The charging and discharging range was 2.8V to 4.25V. Cyclic test was performed. (3) Negative electrode volume expansion rate test: The thickness T1 of the prepared negative electrode was measured; after a 0.5C long cycle test, the soft pack battery was disassembled and the negative electrode thickness T2 was measured; the volume expansion rate = T2 / T1×100% was calculated based on T1 and T2. All the above volume expansion rate tests were carried out at 25℃.

[0032] Table 1. Performance of the pouch cells in the examples and comparative examples.

[0033] Formula I': CAS No.: 2285-12-3; Formula I'': CAS No.: 1548-13-6; Formula VII': CAS No.: 15570-12-4; Formula VII'': CAS No.: 4867-37-2; As shown in Table 1 above, the volume expansion rate of the pouch cells prepared in Examples 1-6 is significantly lower than that of the pouch cells in Comparative Examples 1-3, indicating that additives I-VI form a stable SEI film on the surface of the negative electrode, suppressing the volume expansion of the silicon-carbon negative electrode during cycling. The capacity retention rates of Examples 1-6 in the 0.5C and 1C long-cycle tests are significantly better than those in Comparative Examples 1-3, indicating that additives I-VI effectively improve the cycle performance of the pouch cells, and the formed SEI film is relatively stable, especially additive II, which has the best performance. The pouch cells in Examples 7-15 show further improvements in both volume expansion rate and cycle performance compared to Examples 1-6, indicating a certain synergistic effect between additives I-VI and additives VII-IX. The performance of the pouch cells in Comparative Examples 4-9 was not only not improved compared to Examples 1-6, but was also reduced, or even if there was some improvement, it was very limited. This indicates that the presence of active hydrogen or electron-withdrawing groups on the phenyl sulfide will be detrimental to the complexation effect of the phenyl sulfide shown in structural formula B and the trifluoromethyl-containing phenyl isocyanate shown in structural formula A.

[0034] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. An electrolyte additive, characterized in that, Including trifluoromethyl-containing benzene isocyanates as shown in structural formula A: Where the number of substituents a is any integer from 0 to 4, and any R 1 An electron-withdrawing group that is independently any one of halogen, haloalkane, cyano, nitro, sulfone, sulfonic acid, carboxyl, or ester.

2. The electrolyte additive according to claim 1, characterized in that, The trifluoromethyl-containing benzene isocyanate shown in structural formula A is at least one of the following structural formulas I-VI: 。 3. The electrolyte additive according to claim 1 or 2, characterized in that, It also includes phenyl sulfide, as shown in structural formula B: Where the number of substituents b is any integer from 0 to 5, and any R 2 An electron-donating group that is independently any one of alkyl, alkoxy, alkylamino, aryloxy, or thioether groups, R 3 It is a C1-C6 alkyl or aryl group.

4. The electrolyte additive according to claim 3, characterized in that, The phenyl sulfide represented by structural formula B is at least one of the following structural formulas VII-IX: 。 5. The electrolyte additive according to claim 3, characterized in that, The mass ratio of the trifluoromethyl-containing benzene isocyanate shown in structural formula A to the phenyl sulfide shown in structural formula B is 3-5:

1.

6. A lithium-ion battery electrolyte, characterized in that, It includes lithium electrolyte salts, organic solvents, and electrolyte additives as described in any one of claims 1-5.

7. The lithium-ion battery electrolyte according to claim 6, characterized in that, The electrolyte lithium salt is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, or lithium difluorooxalate borate. The amount of the electrolyte lithium salt added is 8-15% based on the total mass of the electrolyte.

8. The lithium-ion battery electrolyte according to claim 6 or 7, characterized in that, The organic solvent is at least one of organic esters, alkyl ethers, cyclic ethers, sulfones, dinitriles, and ionic liquids; The organic esters are at least one of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, butenyl carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, propyl propionate, ethyl propionate, ethyl acetate, methyl acetate, or γ-butyrolactone; the alkyl ethers are at least one of 1,2-dimethoxyethane, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, or 1,3-dioxolane; the cyclic ethers are at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 4-methyl-1,3-dioxolane, or crown ethers; the sulfones are at least one of sulfolane, methyl sulfolane, ethyl methyl sulfone, or dimethyl sulfone; the dinitriles are at least one of succinic anionibacterium, adiponitrile, glutaronitrile, or 3-methoxypropionitrile; and the ionic liquids are at least one of imidazoles, pyrroles, quaternary ammonium salts, or quaternary phosphonium salts. The amount of organic solvent added is 70-92% based on the total mass of the electrolyte.

9. The lithium-ion battery electrolyte according to claim 6 or 7, characterized in that, The amount of electrolyte additive added is 0.1-5 wt% based on the total mass of the electrolyte.

10. A lithium-ion battery, characterized in that, It includes a negative electrode, a positive electrode, a separator disposed between the negative electrode and the positive electrode, and the electrolyte according to any one of claims 6-9.